INTERVAL METHODS OF ASSIGNING THE NOMINAL TOLERANCES AND CHOOSING ELEMENTS - Shilo, Galina; Gaponenko, Nikolay (International Journal of Computing, 2014)
The procedure of assigning the nominal tolerances is offered. The interval-structure models are used. The influence of exposures is taken into account. The maximum relative volume of tolerances is ensured. The possibility of selecting elements is taken into account.